Effects of Brix, processing techniques and storage temperature on the quality of carambola fruit cordial - Yusof, Salmah; Chiong, Lee Kok (Elsevier Science, 1997)
Two methods of processing carambola fruit cordial were compared using a cold method (CM) and a hot method (HM). Characteristics of the freshly prepared product were compared. Samples were later prepared at 35 °, 45 ° and 55 ° Brix concentrations and stored at 25 °C and 5 °C. The responses measured during storage were changes in pH, titratable acidity, ascorbic acid content, Brix, viscosity, colour, pulp sedimentation and sensory attributes of colour and taste. The pH remained stable during storage but did not show any correlation with titratable acidity, which fluctuated. The ascorbic acid content decreased. Temperature seemed to have an effect on Brix and viscosity values, colour and pulp sedimentation. The 35 ° and 45 ° Brix CM cordials stored at 5 °C were more acceptable in terms of colour and taste. CM did not seem to be a feasible technique for producing cordial from fresh fruit.